IMPLEMENTATION OF GUIDED IMAGINATION THERAPY TO REDUCE ANXIETY IN PRE-OPERATIVE PATIENTS IN THE WEST PADMANABA WARD OF DR. SARDJITO GENERAL HOSPITAL, YOGYAKARTA - Tuty Aprilia Handayani; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2026)
Background: Surgery is a medical procedure performed by dissecting or opening a body part. Patients undergoing surgery often experience nursing problems such as anxiety. Preoperative patient anxiety requires nursing intervention. One of the non-pharmacological therapies is guided imagery which aims to reduce anxiety before surgery. Based on 2023 data, services in the operating room of Dr. Sardjito General Hospital reached 131.4% or 24,461 surgical procedures, showing a significant increase compared to the previous year. Objective: Describe the implementation of guided imagery therapy in reducing the anxiety scale in preoperative patients in the West Padmanaba ward of Dr. Sardjito General Hospital Yogyakarta. Method: Descriptive case study on one patient with preoperative anxiety. Guided imagery therapy was carried out for 10-15 minutes, three times until the patient was about to undergo surgery. Data were obtained through measuring the anxiety scale with the Hamilton Anxiety Rating Scale (HARS) questionnaire before and after implementation. Results: After three sessions of therapy, the patient's anxiety scale decreased from 25 to 15. Conclusion: It was found that guided imagery therapy was able to reduce the anxiety scale in preoperative patients. Suggestion: Guided imagery therapy can be used as a non-pharmacological alternative to reduce anxiety in preoperative patients.